Luminescence properties of Ce3+- doped borate scintillating glass for new radiation detection material. (August 2021) - Rittisut, W.; Wantana, N.; Butburee, A.; Ruangtaweep, Y.; Padchasri, J.; Rujirawat, S.; Manyum, P.; Kidkhunthod, P.; Yimnirun, R.; Kothan, S.; Kim, H.J.; Prasatkhetragarn, A.; et al.
Abstract: A series of glasses composed (Ce 3+ and Gd 3+ ) co-doped lithium aluminum borate glasses with composition 25Li2 O–5Al2 O3 -XGd2 O3 -(69.5-X)B2 O3 -0.5CeF3 glasses were successfully synthesized by using a conventional melt-quenching technique and characterized through physical, structural and luminescence properties. The optimal doping concentration of CeF3 contents is 0.5 mol% and varying Gd2 O3 concentration for studying the combined effect of dual doped glass. Further, the phenomenon of energy transfer from the host glass in luminescence center was observed by x-rays induced luminescence spectra, as well as from Gd 3+ to Ce 3+ ions are confirmed by photoluminescence emission spectra. The strongest emission intensity of Ce 3+ emission is obtained when the scintillating glass contains 5.0 mol% of Gd2 O3 concentration. From the nano-second decay time of glass exhibit a high potential for using as scintillating materials. Highlights: Ce doped in borate glasses were developed. Highest emission intensity of CeF3 was observed at 0.5 mol%. The strongest emission band of X-rays induced luminescence is around 398 nm. To the XANES results confirmed all Ce was present as Ce 3+ and Ce 4+ . The decay times of glass were reported in the nanoseconds order.